Cross-Docking Practices and Distribution Efficiency in Senegal - Ndiaye, Aminata (International Journal of Supply Chain and Logistics, 2025)
Purpose: The purpose of this article was to analyze cross-docking practices and distribution efficiency in Senegal. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Senegal, cross-docking has notably enhanced distribution efficiency despite infrastructural challenges. Firms employing cross-docking improved operational efficiency by up to 10% and reduced lead times by 13% through better load consolidation and real-time coordination. However, limitations in IT infrastructure and standardized protocols still hinder optimal performance. Overall, while cross-docking is transforming distribution networks, further investments are needed to sustain these gains. Unique Contribution to Theory, Practice and Policy: Just-in-time (JIT) production theory, Supply chain integration theory & Diffusion of innovation (DOI) theory may be used to anchor future studies on cross-docking practices and distribution efficiency in Senegal. Organizations should standardize cross‐docking protocols and invest in advanced IT systems that support real‐time tracking and automated sorting to minimize handling times. Collaborative efforts between government, academia, and industry are essential to tailor these policies to current market realities.